PENGARUH VARIASI FORMULASI DAN WAKTU PENGERINGAN TERHADAP KARAKTERISTIK MINUMAN HERBAL DAUN BELUNTAS DAN DAUN MINT - Dinda Anggie Apriliyani; Sigit Prabawa; Bara Yudhistira (AGROINTEK, 2021)
Beluntas (Pluchea indica L.) leaf is a plant that has high antioxidant compounds, and mint (Mentha piperita L.) leaf contain mentol compounds which can improve the taste of herbal drinks. In the processing, the drying process can affect the functional content of beluntas leaves and mint leaves. This study aims to determine the effect of drying time and the formulation of beluntas leaves and mint leaves on physical (colour), chemical (moisture content, total phenol, and antioxidant activity), and sensory (colour, smell, taste, and overall) properties and to determine the combination of drying time and the formulation of beluntas and mint leaves that provide the best herbal drink. The experimental design carried out in this study used a Completely Randomized Design (CRD) with a combined factor, drying time and formulation of beluntas and mint leaves. The time variation used is 1.5 hours; 2 hours and 2.5 hours. Various formulations of beluntas leaves and mint leaves used were 1:1, 2:1, and 3:1. The results showed that the treatment of variations in drying time and the formulation of beluntas and mint leaves had a significant effect on physical (a* and °Hue values), chemical (moisture content, total phenol, and antioxidant activity), and sensory (colour) characteristics. The best treatment in making herbal drink from beluntas and mint leaves is with 1.5 hours drying time and the formulation is 1:1.